Construction of mathematical knowledge school students in six schools state of Lima (a look from the kids) - Aliaga Tovar, Jaime (2014)
The poor performances in Peruvian scholars’ mathematics have their origin in the elementary grades and the subjective construction of mathematical knowledge by the child. The sample of 60 children from third grade six state educational institutions with high and low performance in mathematics. The methodological approach corresponds to grounded theory. Data were collected through focus group. Among the main points about the meaning of mathematical knowledge are: the mathematics memorize in the formal education with the educational ones; it is preferable to have a teacher to a professor; in the home he/she is the support to carry out the school tasks; in the imaginary one family the mathematics and the language are the most important thing and they are linked with the intellectual capacity.